Does environmental administrative penalty promote the quantity and quality of green technology innovation in China? Analysis based on the peer effect - Chen, Xuan; Zhan, Meng (Frontiers in Environmental Science, 2022)
As the guarantee for the effective implementation of environmental policies, the spillover of the deterrent effect of environmental administrative penalties is crucial for solving the environmental regulatory dilemma. It is also unclear whether environmental administrative penalties can affect green technology innovation of the peer enterprises and whether they have an impact on both the quantity and quality dimensions. Taking listed firms of heavily polluting industries in China’s Shanghai and Shenzhen A-share from 2016 to 2020 as the sample, this paper analyzes the impact of the environmental administrative penalty on the quantity and quality of corporate green technology innovation based on the perspective of peer effect. The results indicate that: 1) Environmental administrative penalty significantly promotes the quantity and quality of peer enterprises’ green technology innovation. 2) Heterogeneity analysis shows that the diversity of penalties, the competitiveness of the penalized enterprises, and the property rights of peer enterprises all contribute to the different impacts of the environmental administrative penalty on the peer enterprises’ green technology innovation. 3) Further analysis shows that the promotion effect will be weakened when peer enterprises face high financing constraints. The research results expand the related research on direct government regulation and green technology innovation from the perspective of peer effect and provide policy reference for the government to formulate differentiated penalty policies according to the heterogeneity of enterprise.